Rho activation patterns after spinal cord injury and the role of activated Rho in apoptosis in the central nervous system - Dubreuil, Catherine I. (The Rockefeller University Press, 2003)
Growth inhibitory proteins in the central nervous system (CNS) block axon growth and regeneration by signaling to Rho, an intracellular GTPase. It is not known how CNS trauma affects the expression and activation of RhoA. Here we detect GTP-bound RhoA in spinal cord homogenates and report that spinal cord injury (SCI) in both rats and mice activates RhoA over 10-fold in the absence of changes in RhoA expression. In situ Rho-GTP detection revealed that both neurons and glial cells showed Rho activation at SCI lesion sites. Application of a Rho antagonist (C3–05) reversed Rho activation and reduced the number of TUNEL-labeled cells by ∼50% in both injured mouse and rat, showing a role for activated Rho in cell death after CNS injury. Next, we examined the role of the p75 neurotrophin receptor (p75(NTR)) in Rho signaling. After SCI, an up-regulation of p75(NTR) was detected by Western blot and observed in both neurons and glia. Treatment with C3–05 blocked the increase in p75(NTR) expression. Experiments with p75(NTR)-null mutant mice showed that immediate Rho activation after SCI is p75(NTR) dependent. Our results indicate that blocking overactivation of Rho after SCI protects cells from p75(NTR)-dependent apoptosis.